A Case of a Metanephric Adenoma of the Kidney Surgically Treated with Robot-Assisted Laparoscopic Partial Nephrectomy. (18th September 2013) - Patel, Raunak D.; Frederick, Luke; Kohler, Tobias; Schwartz, Bradley
Abstract : Metanephric adenomas are a rare neoplasm of the kidney with less than 200 cases reported. We report a case of a metanephric adenoma incidentally found on imaging in a 52-year-old Hispanic female and treated with robot-assisted laparoscopic partial nephrectomy. A brief review of the literature is also included.